From Traditional HR To Digital HR: A Transformation Framework For The Future Workforce - Muhammad Syafri; Mhd. Andi Rasyid (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The digital revolution has radically reshaped the landscape of human resource management, demanding a fundamental shift from traditional HR practices to more agile, data-driven, and technology-integrated approaches. This study proposes a comprehensive transformation framework for Digital HR, designed to equip organizations with strategic direction in preparing for the future workforce. By synthesizing literature from strategic HRM, digital transformation, and workforce analytics, the framework outlines key dimensions including digital leadership, cultural agility, HR tech adoption, and data-informed decision-making. Using a qualitative multi-case methodology, data were collected from organizations undergoing digital HR transformations across diverse sectors. Findings reveal that successful transitions depend not only on technological readiness but also on leadership alignment, continuous learning ecosystems, and change management capacity. This framework offers both theoretical contribution and practical guidance for HR leaders navigating the evolving digital landscape, ensuring sustainable workforce development in the era of rapid technological advancement.